Development of a Multivariate Prediction Model for Early-Onset Bronchiolitis Obliterans Syndrome and Restrictive Allograft Syndrome in Lung Transplantation - Koutsokera, Angela; Royer, Pierre J.; Antonietti, Jean P.; Fritz, Andreas; Benden, Christian; Aubert, John D.; Tissot, Adrien; Botturi, Karine; Roux, Antoine; Reynaud-Gaubert, Martine L.; Kessler, Romain; Dromer, Claire; et al. (Frontiers in Medicine, 2017)
Background: Chronic lung allograft dysfunction (CLAD) and its main phenotypes, bronchiolitis obliterans syndrome (BOS) and restrictive allograft syndrome (RAS), are major causes of mortality after lung transplantation (LT). RAS and early onset BOS, developing within 3 years after LT, are associated with particularly inferior clinical outcomes. Prediction models for early onset BOS and RAS have not been previously described. Methods: LT recipients of the French and Swiss transplant cohorts were eligible for inclusion in the SysCLAD cohort if they were alive with at least two years of follow-up but less than 3 years, or if they died or were retransplanted at any time less than 3 years. These patients were assessed for early onset BOS, RAS, or stable allograft function by an adjudication committee. Baseline characteristics, data on surgery, immunosuppression and year-1 follow-up were collected. Prediction models for BOS and RAS were developed using multivariate logistic regression and multivariate multinomial analysis. Results: Among patients fulfilling the eligibility criteria, we identified 149 stable, 51 BOS and 30 RAS subjects. The best prediction model for early onset BOS and RAS included the underlying diagnosis, induction treatment, immunosuppression and year-1 class II donor-specific antibodies (DSAs). Within this model, class II DSAs were associated with BOS and RAS, whereas pre-LT diagnoses of interstitial lung disease and chronic obstructive pulmonary disease were associated with RAS. Conclusions: Although these findings need further validation, results indicate that specific baseline and year-1 parameters, may serve as predictors of BOS or RAS by 3 years post LT. Their identification may allow intervention or guide risk stratification, aiming for an individualized patient management approach.